2008
DOI: 10.1515/cclm.2008.135
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensitive and specific age- and gender-specific low-density lipoprotein cholesterol cutoffs for diagnosis of first-degree relatives with familial hypercholesterolaemia in cascade testing

Abstract: The cutoffs developed here are designed to give the greatest overall accuracy when testing relatives of FH patients in the absence of a genetic diagnosis. They have a more balanced specificity and sensitivity than the MEDPED cutoffs that are designed to achieve higher specificity, which is more appropriate for cascade testing purposes. The data suggest that country-specific LDL-C cutoffs may lead to greater accuracy for identifying FH patients, but should be used with caution and only when a genetic diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 31 publications
4
130
0
9
Order By: Relevance
“…Plasma LDL-cholesterol level alone has excellent discrimination between those with and without FH below the age of 10 years [67,70,71]. However, because of biological variation [29,72], the average of at least two fasting LDL-cholesterol levels should be used to make the diagnosis of FH [19,20,65].…”
Section: Diagnosis and Assessment Of Children And Adolescentsmentioning
confidence: 99%
“…Plasma LDL-cholesterol level alone has excellent discrimination between those with and without FH below the age of 10 years [67,70,71]. However, because of biological variation [29,72], the average of at least two fasting LDL-cholesterol levels should be used to make the diagnosis of FH [19,20,65].…”
Section: Diagnosis and Assessment Of Children And Adolescentsmentioning
confidence: 99%
“…21 While in most cases the genetic test results will not influence the therapeutic strategy, there are several scenarios where the therapeutic route is based on the genetic test result: According to the EAS consensus statement initiation of statin treatment in children at the age of 8-10 is recommended on the basis of a positive genetic test result or strong clinical arguments including LDL-C 4135 mg/dl (43.5 mmol/l). The EAS expert panel advises to offer lipoprotein apheresis in children with homozygous FH.…”
Section: Will Disease Management Be Influenced By the Results Of A Genmentioning
confidence: 99%
“…Of the 15 studies, three (four reports) reported Elucigene FH20, [36][37][38] five (six reports) evaluated LIPOchip, [39][40][41][42][43] four reported LDL-C compared with genetic analysis [44][45][46][47] and three reported ageand gender-specific LDL-C for cascade testing of relatives. [48][49][50] We did not identify any studies reporting a combination of the index tests, that is Elucigene FH20 and LIPOchip.…”
Section: Results Of Test Performancementioning
confidence: 99%
“…In the studies by Starr and colleagues 49 and Mabuchi and colleagues 46 a genetically tested cohort of relatives was recruited to study the test performance of age-and gender-specific LDL-C cut-offs and a cut-off of 4 mmol/l, which is the minimum cut-off required by Simon Broome criteria respectively. In the study by Starr and colleagues, clinically diagnosed index cases based on the Dutch criteria (the Netherlands) and a combination of lipid levels, clinical characteristics and family history (Norway and Denmark) were included, whereas the study by Mabuchi and colleagues 46 included clinically diagnosed index cases based on TC (≥ 5.9 mmol/l and < 12.9 mmol/l) with tendon xanthomata or primary hypercholesterolaemia with/without tendon xanthomata in a family with FH patients among first-degree relatives.…”
Section: Clinical Diagnosismentioning
confidence: 99%
See 1 more Smart Citation